Tribological and electrochemical corrosion behaviors of Cu-based powder metallurgy composites reinforced by in-situ WC with different morphology - Zhiwei Wang; Yu Bian; Junjie Ni; Xiaoqiang Li; Yue Xu; Yuxuan Shao; Jinming Zhen; Liping Cai; Laima Luo (Journal of Materials Research and Technology, 2022)
Tribological and electrochemical corrosion behaviors of copper matrix composites (CMCs) reinforced by the in-situ tungsten carbide with different morphology were investigated in the present work. Compared to the granular and lumpy tungsten carbide, the mesh-structured WC has been found to be more beneficial the wear resistance of CMCs, due in main to its hindrance effect on spalling of copper matrix during friction processes. The hindrance effect is responsible for a 56.0% reduction in the wear rate of CMCs reinforced by mesh-structured WC than those by granular and lumpy WC. Such novel findings provide a method to improve the wear resistance of CMCs, though the mesh-structured WC is easier to induce their electrochemical corrosion. Additionally, the effect mechanism of WC morphology on the materials wear and corrosion behaviors was discussed on the basis of experimental results.